Introduction - Andreas Neef (2018)
© 2007, Springer-Verlag Berlin Heidelberg. Institutional economists have defined institutions as “the rules of the game in a society, or more formally, the humanly devised constraints that shape human action” (North 1990: 3) or as “socially constructed, routine-reproduced, program or rule systems” (Jepperson, 1991: 149). Institutions influence the economic and social behavior of individuals, communities and organizations, and determine the potential for cooperation in resource management. Their function is to expand human choices, enhance the predictability of human behavior (Pejovich, 1995) and establish the basic rules of social transactions. Well-defined institutions contribute to sustainable development by providing more efficient ways of organizing economic activity (Ostrom et al., 1989) and “reduce transaction costs by ameliorating information and enforcement problems” (Burki and Perry, 1998: 143).